Rapid screening of urinary tract infection using microfluidic inertial-impedance cytometry - Petchakup, Chayakorn (2023)
Urinary tract infection (UTI) diagnosis based on urine culture for bacteriuria analysis is time-consuming and often leads to wastage of hospital resources due to false-positive UTI cases. Direct cellular phenotyping (e.g., RBCs, neutrophils, epithelial cells) of urine samples remains a technical challenge as low cell concentrations, and urine characteristics (conductivities, pH, microbes) can affect the accuracy of cell measurements. In this work, we report a microfluidic inertial-impedance cytometry technique for label-free rapid (<5 min) neutrophil sorting and impedance profiling from urine directly. Based on size-based inertial focusing effects, neutrophils are isolated, concentrated, and resuspended in saline (buffer exchange) to improve consistency in impedance-based single-cell analysis. We first observed that both urine pH and the presence of bacteria can affect neutrophil high-frequency impedance measurements possibly due to changes in nucleus morphology as neutrophils undergo NETosis and phagocytosis, respectively. As a proof-of-concept for clinical testing, we report for the first time, rapid UTI testing based on multiparametric impedance profiling of putative neutrophils (electrical size, membrane properties, and distribution) in urine samples from non-UTI (n = 20) and UTI patients (n = 20). A significant increase in cell count was observed in UTI samples, and biophysical parameters were used to develop a UTI classifier with an area under the receiver operating characteristic curve of 0.84. Overall, the developed platform facilitates rapid culture-free urine screening which can be further developed to assess disease severity in UTI and other urologic diseases based on neutrophil electrical signatures.